KARAKTERISIK FISIKOKIMIA TEPUNG KEMBANG KOL HASIL PENGERINGAN DENGAN PENGERING KABINET DAN OVEN [Physicochemical Characteristics of Cauliflower Flour Obtained From Cabinet Dryer and Oven] - Soedirga, Lucia Crysanthy; Matita, Intan C; Wijaya, Terezya E. (Universitas Pelita Harapan, 2020)
Cauliflower is considered as valuable vegetables due to its nutritive value such as dietary fiber. However, fresh cauliflower has short shelf-life. Therefore, conversion of cauliflower into flour through drying process can improve its utilization and nutrition value. This research aims to determine the best drying time of cabinet dryer at 50°C (16, 20, 24 hours) and oven at 70°C (16, 20, 24 hours) toward dietary fibre content, lightness value, and yield. The result shown that 24 hours of drying by using cabinet dryer and 24 hours of drying with oven could produce cauliflower flower with the preferred physicochemical characteristics. Both cabinet dryer and oven with the best drying time was analyzed to produce cauliflower flour with the highest dietary fiber content. Based on the result, cabinet drying at 50°C for 24 hours produce cauliflower flour with the highest dietary fiber content 38.59±0.29%. Moreover, it has 12.43 ± 0.49% of moisture, 11.32 ± 0.34% of ash, 28.88 ± 0.41% of protein, 2.34 ± 0.32% of fat, and 45.04 ± 0.62% of carbohydrate (by difference). AbstrakKembang kol segar memiliki umur simpan yang pendek sehingga pembuatan tepung kembang kol dapat meningkatkan pemanfaatan dan nilai nutrisinya. Penelitian ini bertujuan untuk menentukan waktu pengeringan terbaik dengan menggunakan pengering kabinet 50°C (16, 20, 24 jam) dan oven 70°C (16, 20, 24 jam) terhadap kadar serat, tingkat kecerahan, dan rendemen. Hasil penelitian menunjukkan bahwa waktu pengeringan selama 24 jam dengan pengering kabinet dan oven dapat menghasilkan tepung kembang kol dengan karakteristik fisikokimia yang diinginkan. Tepung kembang kol dengan waktu pengeringan terbaik dari masing-masing pengering kemudian dianalisis kembali untuk menentukan metode pengeringan terbaik dengan kadar serat tertinggi. Hasil menunjukkan bahwa pengering kabinet pada suhu 50°C selama 24 jam mampu menghasilkan tepung kembang kol dengan kadar serat pangan tertinggi sebesar 38,59±0,29%. Selain itu, tepung kembang kol terbaik ini juga memiliki kadar air, kadar abu, kadar protein, kadar lemak, dan kadar karbohidrat (by difference) masing-masing sebesar 12,43 ± 0,49%, 11,32 ± 0,34%, 28,88 ± 0,41%, 2,34 ± 0,32%, dan 45,04 ± 0,62%.